2008
DOI: 10.1038/bmt.2008.73
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum surfactant protein D level prior to transplant for the development of bronchiolitis obliterans syndrome and idiopathic pneumonia syndrome following allogeneic hematopoietic stem cell transplantation

Abstract: Bronchiolitis obliterans syndrome (BOS) and idiopathic pneumonia syndrome (IPS) cause high mortality and impaired survival after allogeneic hematopoietic stem-cell transplantation (allo-HSCT). Early recognition of patients at high risk of developing BOS/IPS may lead to improving the outcome of allo-HSCT. We retrospectively analyzed serum surfactant protein A, D (SP-A, -D) and Kerbs von Lungren 6 Ag (KL-6) levels before allo-HSCT in 56 patients who survived more than 90 days after allo-HSCT and compared values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Furthermore, transtracheal instillation of human SP-A attenuated the manifestations of IPS in mice (137). In humans, pre-transplant serum levels of SP-D were identified as a risk factor for the development of IPS and bronchiolitis obliterans after allogeneic HSCT (138). The investigators speculate that certain polymorphisms in the human SP-D gene cause subnormal levels of SP-D in the alveoli and serum (139).…”
Section: Depletion Of Pulmonary Surfactant During Ipsmentioning
confidence: 99%
“…Furthermore, transtracheal instillation of human SP-A attenuated the manifestations of IPS in mice (137). In humans, pre-transplant serum levels of SP-D were identified as a risk factor for the development of IPS and bronchiolitis obliterans after allogeneic HSCT (138). The investigators speculate that certain polymorphisms in the human SP-D gene cause subnormal levels of SP-D in the alveoli and serum (139).…”
Section: Depletion Of Pulmonary Surfactant During Ipsmentioning
confidence: 99%
“…have shown that SP-D level in the plasma of ALI/ARDS patients was not significantly different when compared to patients without lung injury [63]. Attempts have been made to correlate serum and BAL SP-D levels with human disease, including community-acquired pneumonia in adults, recurrent bronchitis and asthma in pediatric patients, COPD, and smoking [6465], as well as suggesting the use of low serum SP-D levels as a biomarker for the development of bronchiolitis obliterans in hematopoietic stem cell transplant recipients [66]. …”
Section: 4 Sp-d In Human Studiesmentioning
confidence: 99%
“…Recent reports also suggest that biochemical and genetic factors may predispose HSCT recipients to BO, and detection of these factors may lead to earlier recognition of these patients. In a recent multivariate analysis of 56 patients, the authors reported that lower pre‐transplant serum surfactant protein D level, which is a hydrophilic glycoprotein secreted by alveolar type II cells and plays a role as a mediator of innate immunity of the lung, had a trend toward frequent development of BO following HSCT (p = 0.08) (42). Another study showed that single nucleotide polymorphism of genes may increase the risk of BO following HSCT.…”
Section: Risk Factorsmentioning
confidence: 99%